Toward Healthcare 4.0: Industry 4.0 Innovating Hospital Management - de Oliveira, Karine Borges [UNESP]; de Oliveira, Otávio José [UNESP] (World Scientific Publishing, 2024)
Healthcare 4.0 (H4.0) is revolutionizing the way hospitals are managed, bringing innovations to the health service. Therefore, this work proposes the use of drivers aimed at hospital management improvement through H4.0 grounded in a Content Analysis. It resulted in 36 booster elements for hospital management grouped into ¯ve drivers: Process management, Data management, Resource management, Patient management, and Assistance and Development of Healthcare Professionals. These drivers contribute to strengthen the link between the main needs of hospital settings and technologies capable of meeting them in an applied manner. The most signi¯cant scienti¯c contribution of this work lies in deepening and extending the recent block of knowledge on integrating hospital management with H4.0 technologies. Future studies should investigate the application of H4.0 technologies to assist in managing environmental, social and economic sustainability aspects of hospital settings.
Keywords: digital technologies; Healthcare 4.0; healthcare operations management; hospital management; industry 4.0